An Analysis of Theme and Characterization in Jean Webster’s “Daddy-Long-Legs” - Luviana Luviana; Theodore Alexander Atmaja (BLESS, 2026)
This analysis examines the theme and characterization of Jean Webster “Daddy-Long-Legs”. This analysis focused on how the author used characterization to find the theme of the novel. Using a qualitative approach, data were collected through intensive reading and by applying Abrams and Harpham’s (2015) theory of characterization to explore how themes and characters are portrayed in the novel, especially the main character Jerusha Abbott. The researcher discovered the theme of the novel is personal-growth and the characterization of the main character changed from insecure girl into mature woman, and how the related character played important roles in her transformation. This analysis also highlights how an opportunity and support can help individuals overcome struggle and achieve personal growth. This analysis is not only recommended for anyone who is interested in the same topic, but also for students or learners further understanding.